Screening for interaction domain in vault nanocapsules - Vania, Maya (2010)
Protein nanocapsule is gaining popularity as therapeutic delivery vehicle. pH-controlled molecular release from the protein nanocapsule is particularly interesting. Vault is a naturally assembled hollow protein nanocapsule (72 x 41 x 41 nm3) which is composed of major vault protein (MVP) domain that interacts with C-terminus of vault poly(ADP-ribose)-polymerase (VPARP), namely MVP-minimal interaction domain (mINT). The interaction between MVP and mINT is important in engineering the non-native pH-dependent interaction functionality onto the protein nanocapsule. We attempted to identify specific domains that are involved in the interactions between MVP and mINT. From the electron difference map, mINT is hypothesized to associate at the N-terminal MVP at domain 2-5. We constructed four plasmids in E. coli expression vector pET-11a and pET-28a encoding MVP domain 3-4, 3-5, 2-5 and mCherry fused with mINT. These genes were overexpressed to produce protein fractions for validation of interactions. Analysis by SDS-PAGE revealed that majority of protein mCherry-mINT was found in soluble fraction while MVP domain 2-5 was largely presented in pellet form. The use of polyhistidine tag improved the expression of MVP domain 3-5. However, MVP domain 3-4 was not expressed in sufficient quantity to be detected.